Tocilizumab for refractory uveitis associated with juvenile idiopathic arthritis: A report of two cases. (27th February 2019) - Dipasquale, Valeria; Atteritano, Marco; Fresta, Jlenia; Castagna, Irene; Conti, Giovanni
Summary: What is known and the objective: Low‐grade evidence supports the use of newer biologics for otherwise refractory juvenile idiopathic arthritis (JIA)‐associated uveitis, such as tocilizumab. Case summary: This report details the cases of two adolescents whose severe JIA‐associated uveitis was unresponsive to the first‐line therapeutic approach. Tocilizumab therapy led to the remission of uveitis after a mean time of 3 weeks, and methotrexate was safely discontinued 1.5 years later. What is new and conclusion: To our knowledge, these are the first reports of successful methotrexate withdrawal during tocilizumab treatment of JIA‐associated uveitis. The administration of tocilizumab without methotrexate could be considered in patients with JIA‐associated uveitis unresponsive to conventional therapy. Abstract : This article describes authors' experience with tocilizumab (TCZ) for treatment of juvenile idiopathic arthritis (JIA)‐associated uveitis at a paediatric rheumatology referral center, reporting the cases of two adolescents with severe and first‐line therapy‐refractory uveitis associated with positive serum antinuclear antibodies oligoarticular JIA, who responded favorably to TCZ.